2000
DOI: 10.1017/s0033291700001768
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of people with a ‘mental disability’ to make a health care decision

Abstract: Consistent with current views, capacity reflected an interaction between the decision-maker and the demands of the decision-making task. The findings have implications for the way in which decisions about health care interventions are sought from people with a 'mental disability'. The methodology may be extended to assess capacity to make other legally-significant decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
135
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 30 publications
5
135
0
5
Order By: Relevance
“…Three focused on issues to do with communication of information, and found that supporting people to make decisions involves listening to them (Hoole and Morgan, 2011), asking about their preferences and choices in an open and non-challenging way (Antaki, Finlay, Walton & Pate, 2008), and providing clear and simple written information (Wong, Clare, Holland, Watson & Gunn, 2000). The next three studies reported beneficial effects of support training (Koritsas, Iacono, Hamilton & Leighton, 2008;Robertson et al, 2005) and end of life decision support tools for staff (Karp 2009) on patient choice and the quality of support offered.…”
Section: Improving the Implementation Of Supported Decision Makingmentioning
confidence: 99%
See 2 more Smart Citations
“…Three focused on issues to do with communication of information, and found that supporting people to make decisions involves listening to them (Hoole and Morgan, 2011), asking about their preferences and choices in an open and non-challenging way (Antaki, Finlay, Walton & Pate, 2008), and providing clear and simple written information (Wong, Clare, Holland, Watson & Gunn, 2000). The next three studies reported beneficial effects of support training (Koritsas, Iacono, Hamilton & Leighton, 2008;Robertson et al, 2005) and end of life decision support tools for staff (Karp 2009) on patient choice and the quality of support offered.…”
Section: Improving the Implementation Of Supported Decision Makingmentioning
confidence: 99%
“…A practice considered to be less successful was asking for repeated clarifications/checks as this can be interpreted as querying the decision and result in the resident changing their decision. Wong et al (2000) evaluated how simplifying the provision of information affected the ability of people with disability in England to make decisions regarding blood tests. They noted that decision making ability significantly improved as the decision-making tasks were simplified for those with mental health problems, but not for those with intellectual disabilities or dementia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 40 years a number of valuable empirical research studies have been conducted internationally and in the UK, which have attempted to conceptualize the notion of capacity and its assessment (Roth et al, 1977;Weisstub, 1990;Appelbaum and Grisso, 1988;Appelbaum and Grisso, 1995;Wong et al, 1999;Wong et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Severe depression can manifest as impairment of information processing and reasoning that can significantly affect decision making [10]. Compromised ability for decisionmaking capacity has also been associated with disorders like dementia and delirium [11], intellectual disability [12,13], psychosis [14,15], and bipolar disorder [16][17][18]. Additionally, reduced decision-making capacity has been associated with patients admitted involuntarily or patients refusing treatment [15].…”
Section: Influence Of Psychiatric History and Current Diagnosismentioning
confidence: 99%